2017
DOI: 10.5194/amt-10-1769-2017
|View full text |Cite
|
Sign up to set email alerts
|

Carbon monoxide column retrieval for clear-sky and cloudy atmospheres: a full-mission data set from SCIAMACHY 2.3  µm reflectance measurements

Abstract: Abstract. We discuss the retrieval of carbon monoxide (CO) vertical column densities from clear-sky and cloud contaminated 2311-2338 nm reflectance spectra measured by the Scanning Imaging Absorption Spectrometer for Atmospheric Chartography (SCIAMACHY) from January 2003 until the end of the mission in April 2012. These data were processed with the Shortwave Infrared CO Retrieval algorithm (SICOR) that we developed for the operational data processing of the Tropospheric Monitoring Instrument (TROPOMI) that wil… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 33 publications
(69 reference statements)
5
24
0
Order By: Relevance
“…In general, the results in Figure 7 agree with the findings by Borsdorff et al [9,10] within around −5 to −10% for most sites. However, the CO mixing ratios calculated from the BIRRA retrieval have consistently low bias with respect to all sites in both networks, while Borsdorff et al [9,10] found slightly positive biases at some sites.…”
Section: Unweighted Biassupporting
confidence: 82%
See 4 more Smart Citations
“…In general, the results in Figure 7 agree with the findings by Borsdorff et al [9,10] within around −5 to −10% for most sites. However, the CO mixing ratios calculated from the BIRRA retrieval have consistently low bias with respect to all sites in both networks, while Borsdorff et al [9,10] found slightly positive biases at some sites.…”
Section: Unweighted Biassupporting
confidence: 82%
“…However, the CO mixing ratios calculated from the BIRRA retrieval have consistently low bias with respect to all sites in both networks, while Borsdorff et al [9,10] found slightly positive biases at some sites. The data show different magnitudes of biases for different sites.…”
Section: Unweighted Biasmentioning
confidence: 91%
See 3 more Smart Citations